PWE-051 Studies of the psychophysiological markers and the brain processing of nausea in healthy humans using a novel virtual reality video. (28th May 2012) - Ng, K S; Coen, S J; Chua, Y C; Ban, V F; Gresty, M A; Sanger, G J; Williams, S C; Barker, G J; Andrews, P L; Imran, M; Aziz, Q
Abstract : Introduction: Nausea is a common and complex multi-system sensation. Objective psychophysiological markers of nausea that also predict nausea susceptibility in humans are lacking. The regions of the brain that process the sensation of nausea are also unknown. Using a novel model of motion sickness induced nausea, we aimed to study psychophysiological and brain responses during nausea in healthy human volunteers. Methods: A 10-min video of motion and a control video of a still image were presented to 98 healthy volunteers (age 26±8 years, 53 male). Validated questionnaires were used for anxiety and nausea assessment. We monitored sympathetic activity [heart rate (HR) and mean, systolic and diastolic blood pressure (MBP, SBP and DBP)]; parasympathetic activity [cardiac vagal tone (CVT), cardiac sensitivity to baroreceptor reflex (CSB)], electrogastrogram (EGG) and blood cortisol. Comparisons of these parameters were made in the 25 most susceptible and the 25 most resistant subjects (nausea VAS). 28 subjects of the 50 (aged 25±5 years, 16 males, 11 nausea resistant) repeated the experiments with Functional MRI to assess brain activity during nausea. Results: All subjects completed the studies without vomiting. Comparison of motion video (MV) to control: MV raised nausea scores (nausea VAS, +57%±11, pComparison of nausea susceptible (NS) with resistant subjects (NR): the NS subjects showed more parasympathetic withdrawal; larger sympathetic activation and higher cortisol release and trend for higher EGG activity in comparison to NR subjects (Abstract PWE-051 table 1 ). Brain imaging data (all results had corrected p: There was a positive correlation between brain activity and nausea level in the inferior frontal gyrus; and a negative correlation in declive, culmen, cuneus, and parahippocampal gyrus in NS subjects. Compared to NR subjects, NS volunteers showed increased activity in the substantia nigra; and decreased activity in declive and parahippocampal gyrus during nausea induction. Conclusion: NS subjects decreased PNS tone and increased SNS tone, anxiety and cortisol suggesting these parameters could be markers of nausea susceptibility. The NS subjects also showed different brain processing patterns compared to NR subjects. Thus, this safe and effective model for inducing nausea without vomiting can be used to study effects of nausea on GI function together with correlations with objective physiological and brain activity markers. The markers identified may help to reduce and refine animal experiments. Competing interests: None declared.